Forming the mental and disciplinary character of students through extracurricular scouting activities at school - Hanif, Ilyas Saiful; Yunitasari, Dwi (Universitas Kanjuruhan Malang, 2024)
Scout extracurricular is a non-formal extracurricular activity that becomes a place for mental formation and fosters students' disciplinary character. Elementary school is the initial place to foster children's character. This study aims to describe various kinds of implementation, efforts, impacts, and problems of Scout's extracurricular activities in forming elementary school students' mental and disciplinary character. The research method used is descriptive qualitative research, which looks at phenomena that occur in the school field and interviews with related subjects. The results of this study show that Scout extracurricular is a mandatory extracurricular with various forms of fun and educational activities for children. Education in Scouting activities has a positive effect on improving student discipline and mentality. However, issues still need to be solved so that Scouting activities can provide maximum education to students.